Development of an alkaloid–pyrone annulation: synthesis of pleiomaltinine - Kam, T.S.; Ziegler, R.E.; Tan, S.J.; Porco Jr., J.A. (Wiley-VCH Verlag, 2012)
Methodology for the synthesis of alkaloid-pyrones using a novel pyrone annulation of β–carbolines and indoles with 3-siloxy-4-pyrones is reported. The approach has enabled semisynthesis of the unprecedented alkaloid-pyrone pleiomaltinine from the plant-derived indole-alkaloid pleiocarpamine.